Reversible absorptive defects in anticonvulsant megaloblastic anaemia - Reynolds, E. H. (1965)
Two cases of anticonvulsant megaloblastic anaemia are described, showing features of unusual interest. Though both cases were apparently deficient in folic acid, the Figlu tests were negative. One patient had an extremely low serum B(12) concentration apparently associated with defective B(12) absorption due to deficiency of intrinsic factor, and both showed impaired intestinal absorption of D-xylose. There was, however, no evidence of permanent gastro-intestinal dysfunction, and the absorptive defects disappeared completely after treatment with folic acid. Possible reasons for the findings are discussed. It is suggested that absorptive defects produced by the drugs may play some part in initiating anticonvulsant megaloblastic anaemia, and that once deficiencies of haemopoietic factors are established, a vicious circle may be set up owing to the effects of these deficiencies on the gastro-intestinal tract.